2018
DOI: 10.1002/solr.201800198
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Optimization of the Performance of Mn2+‐Doped Kesterite Solar Cell: Machine Learning Aided Synthesis of High Efficient Cu2(Mn,Zn)Sn(S,Se)4 Solar Cells

Abstract: Isoelectronic cation substitution is a potential method to decrease the density of Cu‐Zn anti‐site defects in CZTSSe, thus improving the VOC and performance of CZTSSe solar cells. The proper doping concentration is determined traditionally by the trial and error approach, costing much time, and materials. How to shorten the time to find the proper doping concentration is a big challenge for the development of solar cells. Here, by utilizing the machine learning model, the authors carry out an adaptive design f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 42 publications
(59 reference statements)
2
52
0
1
Order By: Relevance
“…The highest solar cell efficiency is achieved at 5.7% for 15% Mn in CMZTS [150], and 8.9% for 5% Mn in CMZTSSe [151]. The enhancement is attributed to the improved grain growth, better interface between absorber and buffer, and a change in majority defects from Cu Zn to V Cu defects for CMZTSSe [150,151]. As the amount of Mn substitution increases, the carrier concentration increased significantly ( figure 14), and the radiative recombination is quenched, resulting in poor photovoltaic performance for samples with high Mn content [140].…”
Section: Group Vii-b and Viii-bmentioning
confidence: 96%
See 1 more Smart Citation
“…The highest solar cell efficiency is achieved at 5.7% for 15% Mn in CMZTS [150], and 8.9% for 5% Mn in CMZTSSe [151]. The enhancement is attributed to the improved grain growth, better interface between absorber and buffer, and a change in majority defects from Cu Zn to V Cu defects for CMZTSSe [150,151]. As the amount of Mn substitution increases, the carrier concentration increased significantly ( figure 14), and the radiative recombination is quenched, resulting in poor photovoltaic performance for samples with high Mn content [140].…”
Section: Group Vii-b and Viii-bmentioning
confidence: 96%
“…In terms of partial substitution, Cu 2 Mn x Zn 1-x SnS 4 (CMZTS) and Cu 2 Mn x Zn 1-x Sn(S,Se) 4 (CMZTSSe) have been fabricated by different synthesis methods and shown improvement at low Mn substitution [150][151][152][153]. The highest solar cell efficiency is achieved at 5.7% for 15% Mn in CMZTS [150], and 8.9% for 5% Mn in CMZTSSe [151]. The enhancement is attributed to the improved grain growth, better interface between absorber and buffer, and a change in majority defects from Cu Zn to V Cu defects for CMZTSSe [150,151].…”
Section: Group Vii-b and Viii-bmentioning
confidence: 99%
“…In 2012, Chen et al reported a low formation energy for Cu Zn +Sn Zn and 2Cu Zn +Sn Zn in kesterites and also proposed their deleterious role of introducing deep defects and bandgap narrowing. [6,9,11,[20][21][22][23] Here, we study the role of the proposed performance-limiting defects Cu Zn +Zn Cu and 2Cu Zn +Sn Zn by systematically substituting cations in Cu 2 ZnSnS 4 as characterized by both experimental and theoretical methods. [19] Hence, based on theoretical calculations, the possible performance-limiting point defects in kesterites are proposed to be the Cu-Zn antisite Cu Zn +Zn Cu , and the deep-trap-level-inducing Sn-antisite 2Cu Zn +Sn Zn .…”
Section: Introductionmentioning
confidence: 99%
“…So far, solar cells based on Cu 2 MnSnS 4 absorber with conversion efficiencies of up to PCE = 1.8% have been demonstrated . It crystallizes in a tetragonal crystal structure similar to kesterite and has a direct band gap at 1.61 eV and high absorption coefficient .…”
Section: Introductionmentioning
confidence: 99%